Carbon-coated alloy material, negative electrode, sodium-based dual-ion battery and preparation method

By using nitrogen-doped porous carbon-coated alloy metal particle composite material in the negative electrode material of sodium-based bi-ion battery, the problem of expansion and powderization of the negative electrode material after circulation is solved, the conductivity and capacity are improved, and the overall performance and cycle stability of the battery are improved.

CN119581472APending Publication Date: 2025-03-07中汽新能(天津)电池科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411658496.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The negative electrode material of traditional sodium-based dual-ion batteries is prone to expand and powder after multiple charge and discharge cycles, resulting in a sharp attenuation of battery capacity and low conductivity, which affects the cycle stability and performance of the battery.

Method used

A nitrogen-doped porous carbon-coated alloy metal particle composite material is used as the negative electrode active material, and a stable porous carbon structure is obtained by pyrolysis of nitrogen-containing porous organic polymers, which is coated on the surface of alloy metal particles to improve conductivity and capacity.

Benefits of technology

It effectively alleviates the expansion and powderization problems of alloy-type negative electrode materials, improves the conductivity and capacity of the negative electrode, improves the compatibility of the negative electrode active substances and electrolytes, improves the first-effect and rate performance of the battery, and improves the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005142678870000051
    Figure BDA0005142678870000051
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly relates to a carbon-coated alloy material, a negative electrode, a sodium-based dual-ion battery and a preparation method. The preparation method of the carbon-coated alloy material comprises the following steps: adding a nitrogen-containing porous organic polymer into metal powder or a metal salt precursor; and 2) carbonizing to obtain the carbon-coated alloy material. According to the technical scheme, the nitrogen-doped porous carbon coated alloy type metal particle composite material is used as the negative electrode active material to be applied to the sodium-based dual-ion battery, so that the problems of expansion and pulverization of the alloy type negative electrode material after multiple cycles are effectively relieved, and the conductivity of the negative electrode material is improved; the nitrogen-doped porous structure provides more sites and transmission channels for sodium ions, so that the capacity of the negative electrode is improved, the compatibility of a negative electrode active material and an electrolyte is effectively improved, and the first effect and rate capability of the battery are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a carbon-coated alloy material, a negative electrode, a sodium-based dual-ion battery and a preparation method. Background Art

[0002] As the global demand for renewable energy grows, people have higher and higher requirements for the energy density, power density, cost and safety of batteries. Dual-ion batteries are a new type of battery system, in which the positive and negative electrodes simultaneously embed and release anions and cations, thereby realizing battery charging and discharging. They have the advantages of high operating voltage, wide temperature range, good safety, low cost, and environmental friendliness, and have good application prospects in large-scale energy storage and other fields. The electrode material in dual-ion batteries is the key to affecting battery performance: traditional carbon-based negative electrode materials, such as hard carbon, have limited theoretical capacity and low potential platform, and sodium deposition and sodium dendrites are prone to occur on the negative electrode surface, causing battery short circuit; the initial capacity of sodium alloy negative electrode is relatively high, such as the theoretical capacity of tin (Sn) relative to sodium is 847mAh / g, but the volume expansion rate is as high as 423%, and the conductivity is only 9.2*10 -4 S / cm(graphite is 6.5*10 -2 S / cm), the volume expansion and pulverization of the material will seriously affect the cycle stability of the battery, and the low conductivity of the alloy negative electrode also greatly reduces its use value.

[0003] In response to the above problems, the current solutions are: 1) Structural design: The alloy material is made porous through physical and chemical methods such as mechanical molding, chemical etching, laser cutting, plasma etching or chemical etching to alleviate the expansion of the negative electrode material. However, this method has problems such as uneven pore size, uneven distribution, complex process, high equipment requirements and high cost; 2) Adding elastic additives: Elastic additives have a certain ability to resist deformation and form a protective layer on the surface of the alloy material, which can inhibit expansion while alleviating the corrosion of the electrolyte to the alloy material, but the elastic additive will further reduce the conductivity of the material; 3) Carbon coating: The carbon materials currently used to coat the alloy negative electrode are mostly soft carbon, hard carbon, conductive carbon black, graphene, or derived from bio-based materials such as glucose, sucrose, humic acid, cellulose, chitin, and chain organic polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylonitrile, and melamine. The disadvantage is that the pore structure obtained by this method is unstable. After multiple charge and discharge cycles, the pore structure is easily damaged and collapsed, causing the battery capacity to decay sharply. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a carbon-coated alloy material, a negative electrode, a sodium-based dual-ion battery and a preparation method.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a carbon-coated alloy material, characterized in that it includes the following steps: 1) dispersing a nitrogen-containing porous organic polymer into a solvent, and adding a metal powder or a metal salt precursor after the dispersion is uniform to obtain a precursor mixture; 2) drying the precursor mixture to remove the solvent and then performing high-temperature carbonization to obtain the carbon-coated alloy material.

[0007] The nitrogen-containing porous organic polymer is obtained by high-temperature reaction of melamine and aldehyde compounds;

[0008] Preferably, the ratio of melamine to terephthalaldehyde is 1:(1-5), preferably 1:2;

[0009] Preferably, the aldehyde compound is one of terephthalaldehyde, o-phthalaldehyde, isophthalaldehyde, 4,4-biphenyldicarboxaldehyde, 1,3,5-s-tritylaldehyde, glyoxal, malondialdehyde, and succinaldehyde;

[0010] Preferably, the reaction time is 10 to 20 hours, preferably 12 hours, and the reaction temperature is 150 to 220°C, preferably 180°C.

[0011] In step 1), the mass ratio of the nitrogen-containing porous organic polymer to the metal contained in the metal powder or metal salt precursor is (2-5):1; preferably 3:1

[0012] The specific steps of the medium-high temperature carbonization in step 2) are: carbonizing for 4 to 8 hours at 600 to 800° C. in a mixed atmosphere of inert gas and 2 wt % H 2 .

[0013] The metal powder or metal salt precursor is any one of tin powder, stannous chloride, stannous oxalate, tin acetate, tin nitrate; tetraethyl germanate, germanium monoxide, germanium dioxide, hydroxyethyl germanium sesquioxide, spirogermanium; antimony powder, antimony halide, antimony phosphate, antimony sulfate or a mixture thereof.

[0014] The present invention also includes a carbon-coated alloy material obtained by the preparation method.

[0015] The present invention also includes a negative electrode, comprising the carbon-coated alloy material, a negative electrode conductive agent, and a negative electrode binder;

[0016] Preferably, the mass ratio of the carbon-coated alloy material, the conductive agent, and the binder is 7:2:1;

[0017] Preferably, the negative electrode conductive agent is one or two of carbon black, carbon nanotubes, and acetylene black;

[0018] Preferably, the negative electrode binder is a mixture of one or more of SBR, PAA and CMC.

[0019] The present invention also includes a method for preparing the negative electrode, comprising the following steps: dispersing the carbon-coated alloy material, the conductive agent and the binder in water uniformly and then coating the dispersed materials on a copper foil, vacuum drying the copper foil at 80 to 110° C. for 10 to 30 minutes, and rolling the copper foil to obtain the negative electrode.

[0020] The present invention also includes a sodium-based dual-ion battery, comprising a negative electrode, a positive electrode, a separator and an electrolyte.

[0021] The positive electrode is composed of conductive graphite, a positive electrode conductive agent, a positive electrode binder, and an aluminum current collector;

[0022] Preferably, the positive electrode is prepared by the following method: conductive graphite, positive electrode conductive agent and positive electrode binder are uniformly dispersed in NMP solvent in a ratio of 8:1:1, the mixed slurry is coated on an aluminum current collector, and vacuum dried at 120° C. for 15 min and then rolled;

[0023] Preferably, the positive electrode conductive agent is one or both of carbon black and graphene;

[0024] Preferably, the positive electrode binder is polyvinylidene fluoride;

[0025] Preferably, the electrolyte solute is one or more of NaPF6, NaTFSI, and NaFS I; the solvent is one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, acetonitrile, adiponitrile, glutaronitrile, sebaconitrile, 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, p-fluorobenzonitrile, and p-methylbenzonitrile; the additive is one or more of fluoroethylene carbonate, fluoroethyl methyl carbonate, fluorobenzene, succinonitrile, suberonitrile, and sodium difluorooxalatoborate;

[0026] The electrolyte concentration is 1 to 5 mol / L;

[0027] Preferably, the electrolyte solute is NaPF6, the solvent is EC:EMC=1:1, the additive is 2% FEC, and the concentration is 1 mol / L;

[0028] The diaphragm is one of a glass fiber diaphragm, a porous ceramic diaphragm, a porous polypropylene diaphragm and a porous polyethylene diaphragm.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The technical solution of this application uses nitrogen-doped porous carbon-coated alloy-type metal particle composite materials as negative electrode active materials for sodium-based dual-ion batteries, which effectively alleviates the problems of expansion and pulverization of alloy-type negative electrode materials after multiple cycles, improves the conductivity of negative electrode materials, and the nitrogen-doped porous structure provides more sites and transmission channels for sodium ions, improves the capacity of the negative electrode, and effectively improves the compatibility of negative electrode active materials with electrolytes, which helps to improve the first efficiency and rate performance of the battery. In addition, the coated carbon material is obtained by pyrolysis of nitrogen-containing porous polymers, and the pore structure is stable and adjustable, which can further improve the battery cycle stability. The synthesis process is simple, the raw material cost is low, and it is helpful to achieve commercial production. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with embodiments.

[0032] Example 1

[0033] The preparation method of a nitrogen-containing porous organic polymer comprises the following steps: ultrasonically dispersing a certain amount of melamine and terephthalaldehyde into DMSO, wherein the mass ratio of the melamine to the aldehyde compound terephthalaldehyde is 1:2; transferring the mixed solution into a 100mL PTFE bushing, placing the mixed solution in a 100mL high-pressure reactor, reacting the mixture at 180°C for 12 hours, cooling the mixture to room temperature, stirring and washing the reaction solution with an excess of a mixture of methanol and dichloromethane to remove excess unreacted monomers, wherein the ratio of the mixture of methanol and dichloromethane is 1:4, filtering to obtain a white powder, and vacuum drying the mixture at 30°C for 10 hours to obtain a nitrogen-containing porous organic polymer 1.

[0034] Example 2

[0035] The difference between Example 2 and Example 1 is that the mass ratio of melamine to the aldehyde compound is 1:1, and the nitrogen-containing porous organic polymer 2 is obtained.

[0036] Example 3

[0037] The difference between Example 2 and Example 1 is that the mass ratio of melamine to aldehyde compound is 1:5, and the nitrogen-containing porous organic polymer 3 is obtained.

[0038] Example 4

[0039] The difference between Example 4 and Example 1 is that the aldehyde compound is 1,3,5-tribenzaldehyde.

[0040] Example 5

[0041] The difference between Example 5 and Example 1 is that the aldehyde compound is succinaldehyde.

[0042] The nitrogen-containing porous polymer obtained in Examples 1-5 was used to prepare carbon-coated alloy materials.

[0043] The preparation method of the carbon-coated alloy material specifically includes the following steps: ultrasonically dispersing 5g of nitrogen-containing porous polymer (prepared in Examples 1-5) into 200mL of a mixed solution of water and ethanol with a mass ratio of 5:1, adding 15g of SbCl3 after uniform dispersion, and ultrasonically dispersing at 30°C for 3h to obtain a precursor mixture; heating the precursor dispersion to 60°C, stirring at 400r / min until the solvent is almost completely evaporated, and vacuum drying the remaining product at 65°C for 10h, then sending the solid precursor mixture into a tubular furnace, carbonizing at 800°C, in an inert gas / 2wt% H2 atmosphere for 6h, and a heating rate of 2°C / min to obtain a nitrogen-containing porous carbon-coated antimony composite material.

[0044] The above-mentioned nitrogen-containing porous carbon-coated antimony composite material, carbon black, SBR and CMC were uniformly dispersed in water at a ratio of 7:2:0.6:0.4 and coated on copper foil, vacuum dried at 100°C for 20 minutes, and rolled to obtain a negative electrode sheet. Conductive graphite, graphene and PVDF were uniformly dispersed in NMP solvent at a ratio of 8:1:1, and the mixed slurry was coated on an aluminum current collector, and the positive electrode was rolled after vacuum drying at 120°C for 15 minutes. In an inert gas-protected glove box, the positive sheet, glass fiber diaphragm, negative electrode and electrolyte (electrolyte solute is NaPF6, solvent is EC:EMC=1:1, additive is 2% FEC, concentration is 1mol / L) were assembled into a CR2032 button battery.

[0045] Comparative Example 1

[0046] The difference between Comparative Example 1 and Example 1 is that the preparation method of the negative electrode is different; antimony powder, carbon black, SBR and CMC are evenly dispersed in water in a ratio of 7:2:0.6:0.4 and then coated on a copper foil, vacuum dried at 100°C for 20 minutes, and rolled to obtain a negative electrode sheet.

[0047] Comparative Example 2

[0048] The difference between Comparative Example 2 and Example 1 is that the preparation method of the carbon-coated alloy material is different; 1) 5g of melamine is ultrasonically dispersed into 200mL of a mixed solution of water and ethanol with a mass ratio of 5:1, and 15g of SbCl3 is added after uniform dispersion, and ultrasonically dispersed at 30°C for 3h to obtain a precursor mixture; the precursor dispersion is heated to 60°C, stirred at 400r / min until the solvent is almost completely evaporated, and the remaining product is vacuum dried at 65°C for 10h, and then the solid precursor mixture is sent into a tubular furnace, carbonized at 800°C, in an inert gas / 2wt% H2 atmosphere for 6h, and the heating rate is 2°C / min to obtain a carbon-coated antimony composite material.

[0049] Electrochemical performance test: The electrochemical performance test of the dual-ion batteries of Examples 1-5 and Comparative Examples 1-2 was performed respectively, with a voltage range of 2 to 4.7 V and a current density of 0.2 Ag. -1 The current density of the rate test is 0.1A. -1 , 0.2Ag -1 , 0.5Ag -1 , 1A.g -1 , 2A.g -1 , 5A.g -1 , the test results are as follows:

[0050] Table 1 Battery performance test data

[0051]

[0052] Table 2 Battery capacity retention rate at different rates

[0053] 100mA / g 200mA / g 500mA / g 1A / g 2A / g 5A / g Example 1 105% 100% 98% 92% 88% 85% Example 2 105% 100% 96% 93% 80% 75% Example 3 105% 100% 96% 92% 87% 80% Example 4 106% 100% 98% 90% 81% 73% Example 5 103% 100% 96% 90% 87% 80% Comparative Example 1 107% 100% 93% 86% 75% 50% Comparative Example 2 105% 100% 93% 90% 80% 67%

[0054] The results show that the carbon-coated alloy materials prepared in Examples 1-5 are more evenly and completely coated than those in Comparative Example 1-2. They are used as negative electrode active materials in sodium-based dual-ion batteries, which enable the batteries to have higher first coulombic efficiency, cycle capacity retention rate and better rate performance. The rebound rate of the negative electrode sheet is lower after the battery cell is dissected. It is speculated that the pore size of the nitrogen-containing porous polymer is uniform, the distribution is even and the structure is stable after carbonization. The pores coated on the surface of the alloy particles can provide more abundant ion storage sites and transmission channels, and can also provide space for the expansion of the alloy metal particles, effectively reducing the influence of volume expansion on the life of the negative electrode sheet.

[0055] In summary, the technical solution of the present application uses nitrogen-doped porous carbon-coated alloy-type metal particle composite materials as negative electrode active materials for sodium-based dual-ion batteries, which effectively alleviates the problems of expansion and pulverization of alloy-type negative electrode materials after multiple cycles, improves the conductivity of negative electrode materials, and the nitrogen-doped porous structure provides more sites and transmission channels for sodium ions, improves the capacity of the negative electrode, and effectively improves the compatibility of negative electrode active materials with electrolytes, which helps to improve the first efficiency and rate performance of the battery. In addition, the coated carbon material is obtained by pyrolysis of nitrogen-containing porous polymers, and the pore structure is stable and controllable, which can further improve the battery cycle stability. The synthesis process is simple, the raw material cost is low, and it is helpful to achieve commercial production.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-coated alloy material, characterized in that: The method comprises the following steps: 1) dispersing nitrogen-containing porous organic polymer into a solvent, adding metal powder or metal salt precursor after uniform dispersion to obtain a precursor mixture; 2) drying the precursor mixture and then carbonizing it at high temperature to obtain a carbon-coated alloy material.

2. The method for preparing the carbon-coated alloy material according to claim 1, characterized in that: The nitrogen-containing porous organic polymer is obtained by high-temperature reaction of melamine and aldehyde compounds; Preferably, the ratio of melamine to terephthalaldehyde is 1:(1-5), preferably 1:2; Preferably, the aldehyde compound is one of terephthalaldehyde, o-phthalaldehyde, isophthalaldehyde, 4,4-biphenyldicarboxaldehyde, 1,3,5-s-tritylaldehyde, glyoxal, malondialdehyde, and succinaldehyde; Preferably, the reaction time is 10 to 20 hours, preferably 12 hours, and the reaction temperature is 150 to 220°C, preferably 180°C.

3. The method for preparing the carbon-coated alloy material according to claim 1, characterized in that: In step 1), the mass ratio of the nitrogen-containing porous organic polymer to the metal contained in the metal powder or metal salt precursor is (2-5):1; preferably 3:

1.

4. The method for preparing the carbon-coated alloy material according to claim 1, characterized in that: The specific steps of the medium-high temperature carbonization in step 2) are: carbonizing for 4 to 8 hours at 600 to 800° C. in a mixed atmosphere of inert gas and 2 wt % H 2 .

5. The method for preparing the carbon-coated alloy material according to claim 1, characterized in that: The metal powder or metal salt precursor is any one of tin powder, stannous chloride, stannous oxalate, tin acetate, tin nitrate; tetraethyl germanate, germanium monoxide, germanium dioxide, hydroxyethyl germanium sesquioxide, spirogermanium; antimony powder, antimony halide, antimony phosphate, antimony sulfate or a mixture thereof.

6. A carbon-coated alloy material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.

7. A negative electrode, characterized in that Comprising the carbon-coated alloy material according to any one of claims 1 to 6, a negative electrode conductive agent, and a negative electrode binder; Preferably, the mass ratio of the carbon-coated alloy material, the conductive agent, and the binder is 7:2:1; Preferably, the negative electrode conductive agent is one or two of carbon black, carbon nanotubes, and acetylene black; Preferably, the negative electrode binder is a mixture of one or more of SBR, PAA and CMC.

8. A method for preparing a negative electrode according to claim 7, characterized in that: The method comprises the following steps: uniformly dispersing a carbon-coated alloy material, a conductive agent and a binder in water and then coating the dispersed materials on a copper foil; vacuum drying the copper foil at 80 to 110° C. for 10 to 30 minutes; and rolling the copper foil to obtain a negative electrode.

9. A sodium-based dual-ion battery, characterized in that: It comprises the negative electrode, the positive electrode, the separator and the electrolyte as described in claim 7.

10. The sodium-based dual-ion battery according to claim 9, characterized in that: The positive electrode is composed of conductive graphite, a positive electrode conductive agent, a positive electrode binder, and an aluminum current collector; Preferably, the positive electrode is prepared by the following method: conductive graphite, positive electrode conductive agent and positive electrode binder are uniformly dispersed in NMP solvent in a ratio of 8:1:1, the mixed slurry is coated on an aluminum current collector, and vacuum dried at 120° C. for 15 min and then rolled; Preferably, the positive electrode conductive agent is one or both of carbon black and graphene; Preferably, the positive electrode binder is polyvinylidene fluoride; Preferably, the electrolyte solute is one or more of NaPF6, NaTFSI, and NaFSI; the solvent is one or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, acetonitrile, adiponitrile, glutaronitrile, sebaconitrile, 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, p-fluorobenzonitrile, and p-methylbenzonitrile; the additive is one or more of fluoroethylene carbonate, fluoroethyl methyl carbonate, fluorobenzene, succinonitrile, suberonitrile, and sodium difluorooxalatoborate; The electrolyte concentration is 1-5 mol / L; Preferably, the electrolyte solute is NaPF6, the solvent is EC:EMC=1:1, the additive is 2% FEC, and the concentration is 1 mol / L; The diaphragm is one of a glass fiber diaphragm, a porous ceramic diaphragm, a porous polypropylene diaphragm and a porous polyethylene diaphragm.